Mapping IPF helps identify geographic regions at higher risk for disease development and potential triggers. Issue 4 (9th November 2020) - Shull, Jessica Germaine; Pay, Maria Teresa; Lara Compte, Carla; Olid, Miriam; Bermudo, Guadalupe; Portillo, Karina; Sellarés, Jacobo; Balcells, Eva; Vicens‐Zygmunt, Vanesa; Planas‐Cerezales, Lurdes; Badenes‐Bonet, Diana; Blavia, Rosana; et al.
ABSTRACT: Background and objective: The relationship between IPF development and environmental factors has not been completely elucidated. Analysing geographic regions of idiopathic pulmonary fibrosis (IPF) cases could help identify those areas with higher aggregation and investigate potential triggers. We hypothesize that cross‐analysing location of IPF cases and areas of consistently high air pollution concentration could lead to recognition of environmental risk factors for IPF development. Methods: This retrospective study analysed epidemiological and clinical data from 503 patients registered in the Observatory IPF.cat from January 2017 to June 2019. Incident and prevalent IPF cases from the Catalan region of Spain were graphed based on their postal address. We generated maps of the most relevant air pollutant PM2.5 from the last 10 years using data from the CALIOPE air quality forecast system and observational data. Results: In 2018, the prevalence of IPF differed across provinces; from 8.1 cases per 100 000 habitants in Barcelona to 2.0 cases per 100 000 in Girona. The ratio of IPF was higher in some areas. Mapping PM2.5 levels illustrated that certain areas with more industry, traffic and shipping maintained markedly higher PM2.5 concentrations. Most of these locations correlated with higher aggregation of IPF cases. Compared with other risk factors, PM2.5 exposure was the most frequent. Conclusion: In this retrospective study, prevalence of IPF is higher in areas of elevated PM2.5 concentration. Prospective studies with targeted pollution mapping need to be done in specific geographies to compile a broader profile of environmental factors involved in the development of pulmonary fibrosis. Abstract : This study identifies geographic regions of notable air pollution, juxtaposed over locations with higher prevalence of idiopathic pulmonary fibrosis (IPF). Certain areas with elevated air pollutants may be deserving greater analysis for screening of IPF and optimizing early identification. Prospective studies are required for evaluating air pollution as an IPF risk factor. See related Editorial